Digital transformation of education and modern educational technologies - E. V. Evenko; O. A. Glivenkova (Вестник Майкопского государственного технологического университета)
The article discusses the relevance of digital transformation in the learning process in higher educational institutions. The authors of the article have identified the problem of digital transformation of higher education and established contradictions between the continuous increase in the requirement for the availability of various forms of education (blended, hybrid, distance learning) and the quality of professional training of students. The authors have identified the main problems associated with transformation in the field of modern education: the phenomenon of «clip thinking», the crisis of text culture. The purpose of the research is to identify the pros and cons of digital education at a university by analyzing the use of digital technologies in the design of new educational material. The method of theoretical analysis and pedagogical modeling have been used in the research. The authors have concluded that teachers have an ambiguous attitude towards digitalization in Pedagogy: on the one hand, it negatively affects the education system, on the other, on the contrary, it has a positive effect. In conclusion, the results of the study have shown that teaching students general academic skills in the context of the digital transformation of a university environment will improve the quality of the learning process and significantly improve the professional preparation of students.